2017
DOI: 10.1007/s10549-017-4182-z
|View full text |Cite
|
Sign up to set email alerts
|

Basal markers and prognosis in luminal breast cancer

Abstract: PurposeBasal marker expression in triple negative breast cancers identifies basal like tumours, and thus separates the TN group into two prognostic groups. However, the expression and prognostic significance of basal markers in luminal breast cancers are poorly described. The aim of this study was to investigate the expression and prognostic value of basal markers (CK5, CK14 and EGFR) in luminal breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…[40][41][42] We regarded SI ≥ 2 as positive, similar to previous studies of other markers. 25,30,40,43 In addition, we observed nuclear staining in a large proportion of cases, and the proportion of stained nuclei, irrespective of staining intensity was recorded. Not including staining intensity in the assessment of nuclear markers is routine both for hormone receptors and Ki67 in breast cancer.…”
Section: Discussionmentioning
confidence: 64%
“…[40][41][42] We regarded SI ≥ 2 as positive, similar to previous studies of other markers. 25,30,40,43 In addition, we observed nuclear staining in a large proportion of cases, and the proportion of stained nuclei, irrespective of staining intensity was recorded. Not including staining intensity in the assessment of nuclear markers is routine both for hormone receptors and Ki67 in breast cancer.…”
Section: Discussionmentioning
confidence: 64%
“…Regarding the IHC expression of basal CKs, in our study was observed higher percentage of CK5-positive cases than CK14-positive cases (93.1 % versus 44.8 % respectively) regardless of the histological subtype, and the immunoreaction was observed mainly in neoplastic LE cells. In HBC, the CK5 was also more expressed than CK14, although the difference was lower than in CMCs (24.6 % versus 23.3 % respectively) [ 39 ]. Focusing on the proliferating ME cells, mean complex and mixed CMCs, CK5-positive expression was higher (25.9 and 10 %) than the CK14-positive expression (7.4 and 10 %), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining results for CK5/6, CK14, and EGFR were considered positive when > 1% tumor cells were stained. 23,31 The molecular subtypes of TNBCs were defined according to the immunohistochemical results as follows: (1) LAR, AR-positive; (2) BL, CK5/6-positive and/or CK14positive and/or EGFR-positive; (3) UN, tumors with none of the above features. 23,32 The density of CD3 + and CD8 + T-cell infiltration were evaluated in tumor and stroma region with the highest infiltration.…”
Section: B7-h3 and B7-h4 Mrna And Protein Expression In Tnbcmentioning
confidence: 99%